Power Relations in the Sexual Exploitation of Children in the Case of the Rape of Female Islamic Boarding School Students in the City of Bandung - Diwan Azka Purwananda; Muhamad Ibnu Maulana; Muhamad Khaerul Dzikrillah; Ika Arinia Indriyany (Media Hukum Indonesia (MHI), 2026)
This study aims to analyze the role of power relations in the occurrence of child sexual exploitation in the case of the rape of female Islamic boarding school students in Bandung. The research employed a qualitative approach with a critical case study design. Data were collected through document analysis of court decisions, media reports, and relevant academic literature, using a document analysis guideline and source triangulation. Data were analyzed interpretatively to examine the perpetrator’s social position, the victim’s structural dependency, and patterns of domination within the educational institution. The findings reveal that sexual exploitation occurred within socially and symbolically legitimized non-formal power relations, producing structural inequality and limiting the victim’s capacity to resist. The study demonstrates that child sexual exploitation constitutes a structural phenomenon rooted in unequal power distribution within institutions rather than merely an individual criminal act. Strengthening institutional oversight and restructuring power relations are therefore essential for prevention.